Electrochemical characteristics of welded joints on stainless steel - Korać, Fehim; Gutić, Sanjin; Semić, Inesa; Kozica, Indira; Gojak, Sabina; Islamović, Safija; Ostojić, Jelena (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2012)
Maritime atmosphere represents the corrosion environment characterized by air saturated with chloride. Many different factors affect the quality of welded joint and the material around it. In case of welding of steel structures, those factors include selection of the welding process, an additional electrode material, and type of lining. Stainless steel is used for different equipment that is exposed to sea water. Connecting those parts together is done by welding method whose quality depends on a number of factors. Some of those factors are investigated in this study. Samples used in experiments are X5CrNi 18-10ASTMAISI304 stainless steel sheets of austenitic type. This sheet is welded in two different ways: manual arc welding in a protective atmosphere of argon and manual arc welding with covered rutile electrode. Corrosion characteristics have been investigated for three distinct zones: zone of welded joint itself, zone in the vicinity of welded joint and zone far from welded joint (basic material). Tests were performed in 0.9% and 3% NaCl solution, as well as in sea water samples from the area of Dubrovnik and Ploče (brackish water). Electrochemical study has been performed by means of potentiodynamic polarization between -0,150V and 0,350V vs. saturated Ag/AgCl electrode. Results obtained for X5CrNi18-10 austenitic steel and its welded parts in different media at room temperature indicate some degree of self-passivation along with uniform corrosion processes. Based on the obtained results, we concluded that values of corrosion potential lie between 0.350V and -0.150V, depending on the environment in which each sample is probed. In the case of sample welded with dross, increase of corrosion rate does not follow increment of chloride concentration in the expected extent. Corrosion processes are mostly located on the ZUT-OM interface. For the majority of samples, welding in argon atmosphere proved to be a more acceptable way of processing metals from the aspect of corrosion resistance.